Quality Standards or Censorship? Language Control Policies in Cable TV Subtitles in Brazil - Alfaro de Carvalho, Carolina (Meta, 2012)
This study seeks to understand the origins and reasons behind the grammar and style guidelines elaborated by Brazilian broadcasters and video producers and applied to the translated subtitles of cable television shows. The language of the translation is often controlled, and coarse or scatological vocabulary tends to be curbed or avoided, among other restrictions. Brazil was under a military regime from 1964 to 1985, when the media was subjected to strict censorship. Could it be that this heritage still casts a shadow over current policies applied to audiovisual translation (AVT)? To approach this issue, this study outlines the history of censorship applied to content and language during the Brazilian military regime, describes the evolution of the AVT industry in the context of cable television in Brazil, and finally conveys first-hand insights and experiences on language control by quality control professionals. The ultimate goal is to bring these rulemaking processes to light, in an attempt to help improve the dialogue between end clients and service providers, for the benefit of the viewers.